Diagnostic Yield of Comprehensive Coronary Function Testing in Patients with Angina and Unobstructed Coronary Arteries: Endotype Characterisation and Clinical Implications - Johanna McChord; Astrid Hubert; Raffi Bekeredjian; Peter Ong; Andreas Seitz (European Cardiology Review)
Background: Coronary functional disorders (CFD) are significant contributors to angina with non-obstructed coronary arteries (ANOCA). Various endotypes, such as epicardial or microvascular spasm and/or coronary microvascular dysfunction (CMD), have been identified. Previous studies have shown a high prevalence of CFD in ANOCA cases, but often lacked comprehensive coronary functional testing (CFT), which ideally includes coronary spasm provocation testing and CMD assessment. This study aims to investigate the prevalence of CFD and to characterise endotypes in ANOCA patients using comprehensive CFT. Methods: A total of 89 consecutive ANOCA patients (mean age 64, 69% women) who underwent comprehensive CFT were enrolled. CFT comprised acetylcholine (ACh) spasm provocation testing and assessment of coronary flow reserve (CFR) and hyperaemic microvascular resistance using Doppler technique. Results: CFT identified at least one coronary vasomotion disorder in 91% of patients with ANOCA. Among them, microvascular spasm was the most common endotype (61%), followed by CMD (43%). Only 9% of patients had isolated CMD with the remaining CMD patients also showing coronary spasm. Low CFR was mainly associated with high resting coronary flow rather than impaired hyperaemic flow (R −0.60, p<0.0001). Additionally, 48% of patients with microvascular spasm exhibited moderate to severe coronary tortuosity. Conclusion: CFT provides a high diagnostic yield of CFD in ANOCA patients. Coronary spasm, particularly microvascular spasm, is the most frequent endotype. Patients with isolated CMD are rare, highlighting the importance of spasm testing in the ANOCA population.